Opening the dialogue: Research networks between high‐ and low‐income countries further understanding of global agro‐climatic challenges. Issue 2 (2nd February 2019) - Smith, Stephanie; Bandyopadhyay, Tirthankar
Abstract : Societal Impact Statement In the modern world it has become increasingly urgent to balance human food security needs with environmental needs. These needs are not necessarily mutually exclusive, and can be synergistic. The Cambridge‐India Network for Translational Research in Nitrogen (CINTRIN) seeks to reduce nitrogen fertilizer overapplication (and the resulting environmental pollution) in Indian agriculture: a situation with various scientific and sociopolitical drivers, which equally have various sociopolitical and scientific solutions. By listening to the needs of local farmers and applying the knowledge and resources of global plant science research, achieving higher crop yields with less nitrogen is an achievable prospect for India. Abstract : In the modern world it has become increasingly urgent to balance human food security needs with environmental needs. These needs are not necessarily mutually exclusive, and can be synergistic. The Cambridge‐India Network for Translational Research in Nitrogen (CINTRIN) seeks to reduce nitrogen fertilizer overapplication (and the resulting environmental pollution) in Indian agriculture: a situation with various scientific and sociopolitical drivers, which equally have various sociopolitical and scientific solutions. By listening to the needs of local farmers and applying the knowledge and resources of global plant science research, achieving higher crop yields with less nitrogen is an achievable prospect for India.